Vasopressin Plasma Concentrations Are Not Associated with Hemodynamic Response to Exogenous Vasopressin for Septic Shock. Issue 1 (28th November 2019) - Yerke, Jason R.; Sacha, Gretchen L.; Scheraga, Rachel G.; Culver, Daniel A.; Abraham, Susamma; Torbic, Heather; Lam, Simon W.; Ammar, Mahmoud A.; Olman, Mitchell A.; Bauer, Seth R.
Abstract : Introduction: Positive hemodynamic response to vasopressin after 6 hours of infusion was independently associated with lower mortality in a previous retrospective study of patients with septic shock. However, factors previously associated with higher plasma vasopressin concentration were not associated with response, and the relationship between plasma vasopressin concentration and hemodynamic response has not been evaluated. Objectives: This cross‐sectional study compared plasma vasopressin concentrations in hemodynamic responders and nonresponders to vasopressin in patients with septic shock to evaluate plasma vasopressin concentration as a therapeutic target for hemodynamic response to vasopressin. Methods: Adult patients with septic shock were included if they were treated with fixed‐dose vasopressin as an adjunct to catecholamines for at least 3 hours. Patients were assigned to groups based on vasopressin response. Results: Ten hemodynamic responders to vasopressin and eight nonresponders were included. Blood samples for plasma vasopressin concentration were collected 3–6 hours after vasopressin initiation. Baseline characteristics were similar between groups. No difference was detected in plasma vasopressin concentrations between hemodynamic responders and nonresponders (median 88.6 pg/ml [interquartile range (IQR) 84.4–107.5 pg/ml] vs 89.9 pg/ml [IQR 67.5–157.4 pg/ml], p=0.79, respectively). We also did not detect a difference between groups after correcting for vasopressin dose; median vasopressin plasma concentration per 0.01 units/minute of vasopressin infusion for responders was 25.9 pg/ml (IQR 21.8–31.8 pg/ml) versus 29.5 pg/ml (IQR 23.0–57.5 pg/ml, p=0.48) for nonresponders. No difference in clinical outcomes was detected between groups. The findings were robust to multiple sensitivity analyses. Conclusions: This study does not support the use of plasma vasopressin concentrations as a therapeutic target to predict hemodynamic response to exogenous vasopressin in septic shock.